2005
DOI: 10.1590/s1516-14392005000400011
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evaluation of rare-earth-zinc oxide-based varistor ceramics

Abstract: Zinc oxide varistors are nonlinear voltage dependent ceramic resistors used to suppress and limit transient voltage surges. The work reported in this paper involves the relationship between microstructural characteristics and the varistor performance of ZnO ceramics doped with rare-earth oxides. Samples of these ceramics with different nonlinear current-voltage characteristics, according to the specific chemical composition and sintering parameters, were prepared and microstructurally analyzed by scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
4
0
8
Order By: Relevance
“…Based on the recent trend, Pr 6 O 11 based ZnO ceramics have been actively researched to overcome drawbacks in existing Bi 2 O 3 based ZnO varistor materials such as Bi 2 O 3 vaporization and formation of Bi-containing secondary phases when sintered at temperatures over 1000 °C [1620]. Ramirez et al , [16] and Furtado et al , [17] demonstrated that Pr 6 O 11 improved effective electrical current flow by restraining the formation of secondary phases and induced densification of varistor during fabrication. Zhu et al , [18] claimed that Pr 6 O 11 exhibited grain growth suppressing effect that controlled the overall development of grain during sintering.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the recent trend, Pr 6 O 11 based ZnO ceramics have been actively researched to overcome drawbacks in existing Bi 2 O 3 based ZnO varistor materials such as Bi 2 O 3 vaporization and formation of Bi-containing secondary phases when sintered at temperatures over 1000 °C [1620]. Ramirez et al , [16] and Furtado et al , [17] demonstrated that Pr 6 O 11 improved effective electrical current flow by restraining the formation of secondary phases and induced densification of varistor during fabrication. Zhu et al , [18] claimed that Pr 6 O 11 exhibited grain growth suppressing effect that controlled the overall development of grain during sintering.…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, com base nos resultados apresentados na Figura 8 e na caracterização elétrica apresenta em outros trabalhos, (4,7,9) nota-se claramente que os parâmetros que caracterizaram o melhor desempenho elétrico, obtidos com 1,0% molar de óxido de terras-raras, estão diretamente relacionados ao maior grau de densificação alcançado. Adicionalmente, as relações entre a espessura média das CIG -obtida para um total de dez medições com base em fotomicrografias dos sistemas considerados -, o percentual médio de área de uma fotomicrografia ocupado por CIG e precipitados de terras-raras (excetuando-se porosidades) -também obtido com base nas medições em fotomicrografias, como acima considerado -, e o teor de óxido de terras-raras são lineares e crescem fortemente com o aumento deste teor.…”
Section: Figuraunclassified
“…Dessa forma, na literatura são encontrados diversos trabalhos sobre a adição de dopantes e uso de diferentes rotas de processamento que culminam na melhoria das propriedades do material varistor. (7,8,9,10,11) Neste trabalho foram avaliadas a microestrutura e a composição de um material varistor comercial a fim de se comparar os resultados obtidos com a literatura. Também foram usados diferentes tipos de ataque ceramográfico para revelação da microestrutura a fim de se determinar qual fornece um melhor resultado para a análise das imagens obtidas por MEV.…”
Section: Introductionunclassified